Reinkes'edema: Immunoexpression study of fibronectin, laminin and colagen IV in 60 cases by imunohistochemical techniques - Martins, Regina Helena Garcia [UNESP]; Domingues, Maria Aparecida [UNESP]; Fabro, Alexandre Todorovic [UNESP]; Dias, Norimar Hernandes [UNESP]; Santana, Marcela Ferreira [UNESP] (Elsevier, 2009)
Reinke's edema is chronic laryngeal disease in which the superficial layer of the lamina propria is expanded by thick mucus, giving it a gelatin aspect. The disease is directly related to smoking and more frequent in women, who end up having a lower tone of voice. Its histological characteristics cannot always distinguish it from other benign lesions of the larynx for which additional histological techniques are necessary. Aim: to study the immunoexpression of fibronectin, collagen IV and laminin in Reinke's edema by immunohistochemical technique. Prospective study. Materials and methods: histological blocks of 60 cases of surgical Reinke's edema were saved, submitted to new cross-sections and to immunohistochemical reactions for fibronectin, laminin and collagen IV by the Avidin-Biotin-Peroxidase method. Fragments of five normal vocal folds were used as control, removed during autopsy. All patients were chronic smokers and adults- 50 women and 10 men. Results: the immunoexpression of fibronectin, collagen IV and laminin was more important in the endothelium of blood vessels (68.33%, 76.66%, 73.33%, respectively) and less relevant in the basement membrane (25.0%, 5.0% and 3.3%, respectively). Conclusions: the immunoexpression of fibronectin, laminin and of collagen IV in the basal membrane of Reinke's edema was not relevant, with a predominance of these antibodies in the endothelium of blood vessels. © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Edema de Reinke: Estudo da imunoexpressão da fibronectina, da laminina e do colágeno IV em 60 casos por meio de técnicas imunoistoquímicas
Keywords: Fibronectins; Immunohistochemistry; Laminin; Laryngeal edema; Type iv collagen